ChemInform Abstract: Manganese Catalyzed C—H Functionalization of Indoles with Alkynes to Synthesize Bis/trisubstituted Indolylalkenes and Carbazoles: The Acid is the Key to Control Selectivity. Issue 34 (August 2015) - Shi, Lijun; Zhong, Xiang; She, Houde; Lei, Ziqiang; Li, Fuwei
Abstract C—H alkenylation reactions of indoles with terminal‐ and internal alkynes are presented.